Réponses

  • Omnes
  • Modérateur confirmé
2014-03-10T21:35:43+01:00
Salut,

Tu sais qu'un produit de facteurs est nul si et seulement si un des termes est nul.

a)

(3x-5)(2x+6) = 0
3x - 5 = 0
3x = 5
x = 5/3

2x + 6 = 0
2x = -6
x = -6/2
x = -3

S={-3;5/3}

b)
(4x + 3)(x-5)(5-3x) = 0
4x + 3 = 0
4x = -3
x = -3/4

x - 5 = 0
x = 5

5-3x = 0
5 = 3x
x = 5/3

S = {-3/4;5/3;5}
c)

(4x-1)(2x+3) - (2x+3)(3+15) = 0
(4x-1)(2x+3) - 18(2x+3)=0
(2x+3)|4x-1 - 18] = 0
(2x + 3)(4x - 19) = 0
2x + 3 = 0
2x = -3
x = -3/2

4x - 19 = 0
4x = 19
x = 19/4
S = {-3/2; 19/4}

d)

2x * (x+1)/7 = 0

(2x² + 2x )/ 7 = 0
2x² + 2x = 0
2x(x+1) = 0
2x = 0
x = 0
x + 1 = 0
x = -1

S = {-1;0}

Bonne nuit !